A cross sectional study on the impact of coronavirus disease-19 pandemic on the training of interns in a Medical College Hospital, Andhra Pradesh, India - Roopa Suresh; A C Sanjay Reddy; Suresh Krishnamurthy; R Anil; Y J Visweswara Reddy; P Janakiraman; P J Harsha; H R Krishna Rao; V S Subba Rao Ryali (Wolters Kluwer Medknow Publications, 2023)
Background: A Medicine and Bachelor of Surgery (MBBS) graduate will gain the required skills and competencies under supervision during the internship training. Many factors influence the competency levels. Coronavirus disease-19 (COVID-19) pandemic could be one of those factors. Objectives: The objectives were to assess the competency levels among medical interns, postinternship, during the COVID pandemic and also to assess the association between the competency levels with their final year results. Subjects and Methods: A cross-sectional study was conducted among 113 interns using a self-assessment questionnaire. Self-perception about the competencies was graded into three categories as low, moderate, and high. The Chi-square test was used for analysing statistical association between self-perception and MBBS final year part II results. Results: The level of self-perception about the competencies among the interns was found to be high in-analysis, display and interpretation of information; hypothesis formulation and decision-making (45.1%) and interpersonal communication, management, organizing health care system and professionalism (42.5%), whereas it was low for obtaining information from the patients and their families (29.2%) and procedural skills (18.6%). About 75.2% and 76.1% of the interns had low self-perception for endo-tracheal intubation and lumbar puncture, respectively. High level of self-perception was noted for urethral catheterization (84.2%) and intramuscular drug administration (76.1%). It was found that none of the competencies were statistically associated with the grade based on marks obtained in final year part II. Conclusion: COVID pandemic has affected the interns training to a significant extent. There was no statistically significant association between final year grades and the competencies.